Strategy of the General Election Commission of Mandailing Natal Regency in Socializing the 2024 General Election - Anton Aswin Lubis; Syafruddin Ritonga; Walid Musthafa Sembiring (Universitas Medan Area, 2025)
This study focuses on the challenges in socializing the 2024 General Election in Mandailing Natal Regency, influenced by the diverse geography, ranging from coastal to mountainous regions. This creates accessibility issues, especially in remote areas, requiring extra time and cost and having limited infrastructure. The research aims to analyze the strategies the General Election Commission (KPU) implemented in socializing the 2024 General Election and the barriers faced. Based on Chandler's theory (2015), the results show that the KPU's strategies have been effective, with volunteer programs involving religious communities, such as Islamic boarding schools. The appropriate actions also contribute to increasing public understanding of the election process. However, resource allocation presents a challenge, as evidenced by Adhoc Committee members' lack of emotional attachment, not having strong ties to the organization, limited funding, and insufficient understanding among Adhoc members. More intensive training is needed to address these challenges.